American sociology of religion : histories - Blasi, Anthony J. (Religion and the social order,, 2007)
This is a collection of histories of various aspects of American sociology of religion. The contributions range from descriptions of early dissertations, accounts of changes in theoretical conceptualization, the evolution of studies of particular denominations, to the rise of new areas of inquiry such as globalization, feminism, new religions, and the study of the religious traditions of Latino/a Americans. Taken as a whole, the volume complements rather than duplicates commemorative issues of the relevant journals, which focused on the scholarly organizations in the field. It represents a first effort to develop an organized treatment of the fascinating history of the specialty in the U.S.A.